2018
DOI: 10.1016/j.epsl.2018.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Localised thickening and grounding of an Antarctic ice shelf from tidal triggering and sizing of cryoseismicity

Abstract: 20We observe remarkably periodic patterns of seismicity rates and magnitudes at the Fimbul 21 Ice Shelf, East Antarctica, correlating with the cycles of the ocean tide. Our analysis covers 22 19 years of continuous seismic recordings from Antarctic broadband stations. Seismicity 23 commences abruptly during austral summer 2011 at a location near the ocean front in a 24 shallow water region. Dozens of highly repetitive events occur in semi-diurnal cycles, with 25 magnitudes and rates fluctuating steadily with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Hammer and others (2015) and Lombardi and others (2016) observed hybrid events and attributed their source triggering mechanisms to basal cracking and subsequent seawater filling that was analogous to the infiltration of meltwater under Alpine glaciers (West and others, 2010). Pirli and others (2018) observed seismic signals at a similar frequency, but they attributed the source mechanism to basal stick–slip motion between the ice shelf and a sub-shelf pinning point. Our GNSS observations demonstrated that the vertical ice motion was in phase with the tidal variation (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Hammer and others (2015) and Lombardi and others (2016) observed hybrid events and attributed their source triggering mechanisms to basal cracking and subsequent seawater filling that was analogous to the infiltration of meltwater under Alpine glaciers (West and others, 2010). Pirli and others (2018) observed seismic signals at a similar frequency, but they attributed the source mechanism to basal stick–slip motion between the ice shelf and a sub-shelf pinning point. Our GNSS observations demonstrated that the vertical ice motion was in phase with the tidal variation (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Compared with other PSD-PDFs, only the falling tides produce this relatively narrow, localized peak. There are two possible source mechanisms: i) basal friction along unknown pinning points (e.g., Pirli and others, 2018) or near the grounding line due to the high ice flow speed (Aðalgeirsdóttir and others, 2008), and ii) surface cracking due to an enhanced longitudinal strain rate and tension due to vertical bending (Barruol and others, 2013; Podolskiy and others, 2016). Our GNSS measurements indicate that the vertical and along-flow ice flow speed and the longitudinal strain rate reach their maxima during the falling tide at Langhovde Glacier (Figs 2b and 8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible nonlinear mechanism is that vertical tidal motion causes the grounding line to migrate back and forth sufficiently far as to have an effect on ice flow. Evidence of tidal migration of grounding lines remains relatively sparse but measurements of this process have been inferred via remote sensing (Schmeltz et al, 2001;Brunt et al, 2011;Milillo et al, 25 2017) and cryoseismicity (Pirli et al, 2018). This could give rise to several nonlinearities: firstly this can result in the width of the ice shelf changing as the portion of floating ice changes over one tidal cycle (Minchew et al, 2016).…”
mentioning
confidence: 99%
“…Antarctic ice shelves have also been shown to respond mechanically to both ocean tides as well as tele-tsunamis and distantly generated ocean infragravity waves. Pirli et al (2018) showed that rates and magnitudes of cryogenic earthquakes at the Fimbul Ice Shelf (East Antarctica) fluctuate steadily with the cycles of the ocean tide, showing correlations with tide height and spring tides as well as migration of icequakes landwards during the rising tide. Adalgeirsdottir et al (2008) showed the basal seismicity and velocity of an Antarctic ice stream respond to tidal forcing as far as 40 km upstream.…”
Section: Discussionmentioning
confidence: 99%